Crohn's and Colitis Canada's 2021 Impact of COVID-19 and Inflammatory Bowel Disease in Canada: COVID-19 Vaccines—Biology, Current Evidence and Recommendations. (5th November 2021) - Murthy, Sanjay K; Kuenzig, M Ellen; Windsor, Joseph W; Ghia, Jean-Eric; Griffiths, Anne M; Panaccione, Remo; Seow, Cynthia H; Benchimol, Eric I; Bernstein, Charles N; Bitton, Alain; Huang, James Guoxian; Jones, Jennifer L; et al.
Abstract: The COVID-19 pandemic has ushered a globally focused vaccine development program that produced multiple successful vaccines within a year. Four SARS-CoV-2 vaccines have been approved for use in Canada, using two different technologies, all of which have shown excellent efficacy in reducing the rate of symptomatic COVID-19 infection and 100% efficacy in preventing death from COVID-19. People with inflammatory bowel disease (IBD), like many others with immune-mediated chronic diseases, were excluded from the pivotal trials of these vaccines, leading to early hesitancy by regulatory bodies to endorse administering the vaccines to these groups. However, recent data has shown that the adverse event rate to SARS-CoV-2 vaccine among people with IBD is similar to the general population. Early data has further shown that people with IBD are capable of mounting a robust immune response to SARS-CoV-2 vaccines, particularly following a second dose, whereas the response to the first dose is blunted in those receiving anti-TNF therapy or conventional immunosuppressants (azathioprine, 6-mercaptopurine, methotrexate). Based on these data and evidence from previous vaccine programs among people with IBD, multiple national and international expert panels have recommended that individuals with IBD receive complete vaccination against SARS-CoV-2 as soon as possible.